Chemical Composition Of Modified Cocoyam Flour With Spontaneous Fermentation And Autoclaving-Cooling Cycles To Improved Resistant Starch Content - Wiadnyani, A.A. Istri Sri; Suter, I Ketut; Widarta, I W. Rai (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2018)
This research was intended to identify chemical composition of cocoyam  flour  modified with spontaneous fermentation and autoclaving-cooling cycle in order to increase resistant starch content as functional food source. Increase of usage of modified cocoyam flour as product raw material and food ingredient is expected to improve physical characteristic and chemical characteristic of product resulted as well as to improve its potential as functional food source useful for health. The research did modification of caladium powder consisting of two factors. The first factor spontaneous fermentation method (without spontaneous fermentation F0; and with spontaneous fermentation, F1). The second factor is autoclaving-cooling cycle method consisting of three levels without autoclaving-cooling cycle (T0),  one autoclaving-cooling cycle (T1) and two autoclaving-cooling cycles (T2). All treatments were repeated three times so there were 18 experiment units. Parameter observed in this research include water content, yield, amylase content, starch content and resistant starch. The best result of the research was spontaneous fermentation with following characteristic: yield 20.33%, water content 9.3%, starch content 75.16%, amylose content 25.95% and resistant starch content 13.89% and then was two autoclaving-cooling cycles with following characteristic: yield 18.48%, water content 8.87%, starch content 73.54%, amylose content 26.20% and resistant starch content 13.81%.